Decomposition analysis of output change under new production technology in dairy farming* - KUMAR, VINOD (The Indian Journal of Animal Sciences, 2014)
The study was undertaken to examine the decomposition analysis of output change under new milk technology inMeerut district of Uttar Pradesh. Multistage stratified random sampling was used for selection of sample households. Theinput/output data were collected for 3 seasons, viz. rainy, winter and summer by survey method for the year 1990-91. The study revealed that there exists significant difference between value of milk output between crossbred and local cows (group 1) as well as between crossbred cows and buffaloes (group 2). The effect of technological change was positive in both the cases, though it was much higher in group 1. The contribution of input use difference was quite high in both the cases. Interestingly, the use of concentrates played the most important role associated with new milk production technology. The contribution of labour, though small in magnitude, came as the second most important factor.